Selected Abstracts of the 15th International Workshop on Neonatology and the 40th Congress UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies); Cagliari (Italy); October 24th-26th, 2019 - - (Hygeia Press di Corridori Marinella, 2019)
Selected Abstracts of the 15th International Workshop on Neonatology and the 40th Congress UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies); Cagliari (Italy); October 24th-26th, 2019 • Children of the Middle-Eastern and Mediterranean area: we can do better! ABS 1 • THE TUBULAR DAMAGE MARKERS - NETRIN-1 IN PRETERM NEWBORNS • M. Kamianowska, M. Szczepański, N. Chomontowska, A. Wasilewska (Bialystok, Poland) ABS 2 • CYTOMEGALOVIRUS INFECTION IN THE FIRST DAYS OF LIFE: PREVALENCE IN THE SOUTH SARDINIA FROM 2016 TO 2019 • M. Loddo, A. Scano, S. Fais, G. Serreli, G. Orrù, F. Coghe (Cagliari, Italy) ABS 3 • THE EDUCATIONAL NEED FOR PEDIATRIC FOREIGN BODY AIRWAY OBSTRUCTION AMONG NURSERY AND PRIMARY SCHOOL TEACHERS. A PRELIMINARY STUDY • I. Piras, G. Piras, A. Murgia, P. Isoni, G. Melis (Cagliari and Sassari, Italy) ABS 4 • DOES LEAD (Pb) CONTENT OF LIPSTICKS POSE A HEALTH RISK TO CHILDREN? AN EXPOSURE AND RISK ASSESSMENT IN TURKISH COSMETIC MARKET • A. Berkkan, D.M. Öztaş, O.K. Ulutaş (Ankara, Turkey) ABS 5 • PRENATAL DETECTION OF CENTRAL NERVOUS SYSTEM MALFORMATIONS: OUR MULTIDISCIPLINARY APPROACH • M. Paudice, C.M. Biatta, G. Scaglione, C. Ferrari, C. Massarotti, C.R. Gaggero, L. Peñuela, E. Fulcheri, V.G. Vellone, P. De Biasio (Genoa, Italy) ABS 6 • EARLY DIAGNOSIS OF KLIPPEL-FEIL SYNDROME WITH EXTRA-SKELETAL ANOMALIES, A CASE REPORT • E. Cavallaro, F. Fordiani, S. Ferraresi, P. Amistà, C. Fanni, C. Loddo, C. Lorenzetto, F. Marino, G. Passarella, F. Rigon, D. Padrin, A. Mussari, C. Marcellino, S. Rugolotto (Padua and Rovigo, Italy) ABS 7 • SHOULD SOMATOSTATIN BE USED AS FIRST-LINE AGENT IN MANAGEMENT OF CONGENITAL CHYLOTHORAX? • T.M. William (London, UK) ABS 8 • ENAMEL HYPOPLASIA IN COELIAC CHILDREN: AN EPIDEMIOLOGICAL STUDY • A. Sinesi, S. Cefola, R. Francavilla, G. Orrù, C. Casu (Canosa di Puglia, Barletta, Bari and Cagliari, Italy) ABS 9 • METABOLOMICS IN PATENT DUCTUS ARTERIOSUS: PROPOSAL FOR A PROSPECTIVE STUDY • F. Bardanzellu, F. Mecarini, V. Fanos, P. Neroni (Cagliari, Italy) ABS 10 • LONG-TERM OUTCOMES AND VERY LOW BIRTH WEIGHT: A 16 YEARS EXPERIENCE IN THE NICU OF A.O.U FEDERICO II IN NAPLES • M. Vendemmia, G. Mansi, S. Salomè, A. Romano, L. Capasso, S. Ferraioli, C. Colinet, C. Coppola, F. Raimondi (Naples, Italy) ABS 11 • THE IMPORTANCE OF THE PRESENCE OF OLIGOSACCHARIDES IN MATERNAL MILK: METABOLOMIC RESULTS IN A CASE STUDY OF 80 SAMPLES • A. Lussu, S. Corbu, F. Cesare Marincola, V. Fanos, A. Dessì (Cagliari, Italy) ABS 12 • IMPACT OF HTST PASTEURIZATION OF HUMAN MILK ON THE KINETIC OF DIGESTION OF MACRONUTRIENTS AFTER IN VITRO DYNAMIC DIGESTION • S. Sottemano, G. Maiocco, S. Nebbia, M. Giribaldi, O. Ménard, D. Dupont, A. Deglaire, L. Cavallarin, A. Coscia, E. Bertino (Grugliasco and Turin, Italy; Rennes, France) ABS 13 • CHRONIC INTUSSUSCEPTION DUE TO INFLAMMATORY FIBROID POLYP IN CHILD: A CASE REPORT • L. Chiusaroli, F. Stefanachi, F. Marino, F. Rigon, G. Passarella, C. Loddo, C. Fanni, C. Lorenzetto, C. Ficociello, M. Cananzi, S. Rugolotto (Padua and Rovigo, Italy) ABS 14 • SUPRAVENTRICULAR TACHYCARDIA: IS IT A RISK FACTOR FOR NECROTIZING ENTEROCOLITIS? • F. Mecarini, A. Reali, F. Bardanzellu, P. Totaro, A. Dessì, P. Neroni, V. Fanos (Cagliari, Italy) ABS 15 • DRESS IN AN EPILEPTIC BOY • F. Stefanachi, E. Cavallaro, F. Marino, C. Loddo, C. Fanni, F. Rigon, C. Lorenzetto, G. Passarella, S. Rugolotto (Padua and Rovigo, Italy) ABS 16 • PLACENTAL HISTOPATHOLOGY OF DICHORIONIC DIAMNIOTIC TWIN PREGNANCIES IN RELATION TO INTRAUTERINE GROWTH RESTRICTION AND PERINATAL OUTCOME • G. Scaglione, C.M. Biatta, M. Paudice, C. Toma, C. Calcagno, C.R. Gaggero, F. Buffelli, E. Fulcheri, V.G. Vellone, P. De Biasio (Genoa, Italy) ABS 17 • RETROSPECTIVE STUDY INVESTIGATING THE MANAGEMENT OF PATENT DUCTUS ARTERIOSUS IN NEONATES BORN BEFORE 28 WEEKS OF GESTATIONAL AGE: THE CAGLIARI EXPERIENCE • R. Zucca, F. Bardanzellu, P. Neroni, F. Cau, F. Mecarini, V. Fanos (Cagliari, Italy) ABS 18 • PERSISTENT LEFT SUPERIOR VENA CAVA WITHOUT RIGHT SUPERIOR VENA CAVA IN A NEWBORN • G. Passarella, F. Stefanachi, L. Chiusaroli, F. Marino, C. Loddo, C. Fanni, F. Rigon, C. Lorenzetto, C. Ficociello, E. Reffo, S. Rugolotto (Rovigo and Padua, Italy) ABS 19 • TRAUMATIC OPEN GLOBE INJURY IN A CHILD: A CASE REPORT • B. Mangiola, A. Paratore, L. Chiusaroli, F. Stefanachi, F. Marino, F. Rigon, G. Passarella, C. Loddo, C. Fanni, C. Lorenzetto, C. Ficociello, S. Rugolotto (Rovigo and Padua, Italy) ABS 20 • A QUALITY IMPROVEMENT INTERVENTION TO DECREASE HYPOTHERMIA IN PRETERM NEONATES • S. Ferraioli, L. Capasso, J. Cerullo, M. Vendemmia, L. Lepore, C. Grande, C. Coppola, M. Palma, C. Coline, F. Wiedemann, F. Raimondi (Naples, Italy) ABS 21 • THE CURIOUS CASE OF AN UNPLANNED OUT-OF-HOSPITAL BIRTH OF A NEWBORN WHO WAS ABANDONED AFTERWARD IN A GRAVEYARD • F. Stefanachi, L. Chiusaroli, F. Marino, F. Rigon, G. Passarella, C. Loddo, C. Fanni, C. Lorenzetto, C. Ficociello, R. Mattei, S. Rugolotto (Padua, Rovigo and Adria, Italy) ABS 22 • IS RENAL SCINTIGRAPHY ACCURATE ENOUGH TO DIAGNOSE CONGENITAL SOLITARY KIDNEY? EVALUATION OF PRELIMINARY DATA • F. Guerra, M. Rossano, G. Boz, V. Manca, P. Guglielmo, M. Boero, G. Masnata (Cagliari, Italy) ABS 23 • OVERVIEW OF SOLITARY FUNCTIONING KIDNEY: ANALYSIS OF SARDINIAN POPULATION • F. Guerra, G. Boz, M. Rossano, V. Manca, P. Guglielmo, M. Boero, G. Masnata (Cagliari, Italy) ABS 24 • USE OF VACUUM ASSISTED THERAPY IN LLA INFANT WITH ECTIMA: A CASE REPORT • L. Cara, A. Nonnis, A.B. Aru, P. Pistis, R. Mura (Cagliari, Italy) ABS 25 • CONGENITAL ANOMALIES OF THE KIDNEY AND URINARY TRACT (CAKUT): POSTNATAL MANAGEMENT OF URINARY TRACT DILATION • M.L. Giua Marassi, V. Manca, G. Masnata (Cagliari, Italy) ABS 26 • BAD PLACENTA, BAD BRAIN: MATERNAL CHORIOAMNIONITIS ASSOCIATED WITH PRETERM DELIVERY AND INTRAVENTRICULAR HEMORRHAGE • F. Mecarini, C. Gerosa, R. Pintus, V. Marinelli, G. Faa, M. Testa, V. Fanos, C. Betti (Cagliari, Italy) ABS 27 • USE OF ACID SUPPRESSIVE DRUGS IN CHILDREN AND ADOLESCENTS: A SINGLE CENTER EXPERIENCE • G. Cheri, C. Locci, M.G. Clemente, G. Sotgiu, R. Antonucci (Sassari, Italy) ABS 28 • ROTAVIRUS ACUTE GASTROENTERITIS IN HOSPITALIZED CHILDREN: A SINGLE CENTER EXPERIENCE • A. Spano, A.M. Oggiano, M.G. Clemente, G. Sotgiu, R. Antonucci (Sassari, Italy) ABS 29 • URINARY METABOLOMICS IN TERM NEWBORN RELATED TO NUTRITION AND BIRTH WEIGHT: CLINICAL RECORDS • L. Deriu, F. Cesare Marincola, S. Corbu, V. Fanos, A. Dessì (Cagliari, Italy) ABS 30 • OCT-4 IS HIGHLY EXPRESSED IN STEM/PROGENITOR CELLS AND PRIMORDIAL FOLLICLES OF THE HUMAN FETAL OVARY • F. Cau, D. Fanni, M.C. Botta, C. Gerosa, S. Aversa, E. Sorrentino, F. Ronchi, C. Bellan, G. Faa, M. Castagnola (San Gavino Monreale, Cagliari, Siena and Rome, Italy) ABS 31 • CDX2 EXPRESSION IN THE DEVELOPING HUMAN GUT: AN IMMUNOHISTOCHEMICAL STUDY • V. Aimola, C. Gerosa, G. Cerrone, M.S. Piga, G. Senes, R. Murru, M. Scartozzi, G. Faa (Cagliari, Italy) ABS 32 • PLACENTAL MESENCHYMAL DYSPLASIA IN BECKWITH-WIEDEMANN SYNDROME: A CASE REPORT • C. Rossi, M.L. Lai, C. Gerosa, E. Di Felice, V. Fanos, I. Murgianu, F. Birocchi, G. Faa, A. Ravarino (Cagliari, Italy; Philadelphia, PA, USA) ABS 33 • OVERVIEW OF FEDERATED FACILITY TO HARMONIZE AND ANALYZE DATA IN COHORTS • H.S.M. Rajula, V. Odintsova, M. Manchia, V. Fanos (Cagliari, Italy; Amsterdam, the Netherlands; Moscow, Russia; Halifax, NS, Canada) ABS 34 • TUBULAR ADENOMA OF THE BREAST IN A 15-YEAR-OLD GIRL • G. Cerrone, V. Aimola, D. Fanni, C. Gerosa, G. Faa, A. Ravarino (Cagliari, Italy) ABS 35 • PULMONARY CAPILLARY HEMANGIOMATOSIS IN A NEWBORN: A CASE REPORT • G. Cerrone, V. Aimola, G. Masnata, V. Marinelli, M. Testa, F. Coghe, G. Faa, V. Fanos, C. Gerosa (Cagliari, Italy) ABS 36 • HYDROPS DUE TO FETAL TACHYCARDIA: A CLINICAL CASE • D.A. Agostino, R. Thomasset, B. Minervini, A. Di Paolo (Rome, Italy) ABS 37 • ADMISSION LABORATORY TESTING ON UMBILICAL CORD BLOOD HELPS TO REDUCE BLOOD TRANSFUSIONS IN VERY PREMATURE INFANTS • N. Mense-Dietrich, N. Wonko, K. Kalaniti, S. Daspal, V.M. Samedi (Saskatoon, SK, Canada) ABS 38 • COMPATIBILITY OF DEXMEDETOMIDINE AND TOTAL PARENTERAL NUTRITION AT NEONATAL INTENSIVE CARE UNIT: SINGLE CENTRE EXPERIENCE • V. Samedi, H. Hodqson, S. Daspal, L. Givelicheian, W. Bingham, K.